Pengaruh Company Size, Company Growth Dan Profitabilitas Terhadap Nilai Perusahaan (Pada Perusahaan Sektor Industri Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2019-2021) - Sartika, Novi Dewi; Salim, Muhammad Agus; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to test and analyze the effect of company size, company growth and profitability on company value in companies in the food and beverage industry sector which are listed on the IDX for the 2019-2021 period. This research uses Explanative Research. The sample selection for this study used a purposive sampling method using several criteria. From these criteria, companies in the food and beverage sector are listed on the Indonesia Stock Exchange (IDX), companies in the food and beverage industry sector that do not publish annual financial reports consistently on the Indonesia Stock Exchange (IDX) for the 2019-2021 period and companies in the food and beverage sector. did not experience delisting on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The data analysis used was multiple linear regression analysis and used SPSS version 29.0. The results of this study show. Company size has a partially insignificant negative effect on firm value, Company growth has a partially positive and insignificant effect on firm value and Profitability has a partially significant positive effect on firm value Company size, company growth and profitability have a significant positive effect simultaneously on firm value in companies the food and beverage sector listed on the IDX in 2019-2021 Keywords: Company size, company growth profitability and company value.